Magnetic hydroxyapatite nanomaterial–cyclodextrin tethered polymer hybrids as anticancer drug carriers. Issue 10 (15th April 2021) - Ramasamy, Sivaraj; Dhamecha, Dinesh; Kaliyamoorthi, Kiruthiga; Pillai, Archana Sumohan; Alexander, Aleyamma; Dhanaraj, Premnath; Menon, Jyothi U.; Enoch, Israel V. Muthu Vijayan
Abstract : Osteosarcoma, the most common bone cancer, leads to a poor survival rate of patients. Drug targeting employing hydroxyapatite (HAp)-based nanocarriers represents a fascinating choice for non-invasive treatment of osteosarcoma. Abstract : Osteosarcoma, the most common bone cancer, leads to a poor survival rate of patients. Drug targeting employing hydroxyapatite (HAp)-based nanocarriers represents a fascinating choice for non-invasive treatment of osteosarcoma. Herein, we report strontium-doped (Sr-HAp) and iron- and strontium- co -doped (Sr, Fe-HAp) hydroxyapatite nanoparticles as novel materials that deliver doxorubicin to bone cancer cells. A platinum-complexed and cyclodextrin-functionalized chitosan derivative is utilized to coat the NPs. Sr-HAp (aspect ratio ∼20) and Sr, Fe-HAp (aspect ratio ∼3) nanoparticles are formed as nanowhiskers and nanorods, respectively, as revealed by transmission electron microscopy. Strontium ferrite NPs are synthesized and their properties are compared with those of the Sr/Sr, Fe-doped HAp NPs. These ferrite NPs show ferromagnetic behavior, as opposed to Sr-HAp and Sr, Fe-HAp. The latter two respectively display paramagnetic and superparamagnetic behaviors. The loading percentage of the anticancer drug, Doxorubicin (Dox), in the nanocarriers is high and the release of Dox is sustained at physiological pH. The Dox-loaded nanocarriers are tested for their in vitro cytotoxicity against lung, cervical, liver, and bone cancer cell lines. In general, the efficacy of Dox is not diminished on loading in the nanocarriers. In addition, the Dox-carriers demonstrate a time- and dose-dependent cytotoxicity. The efficacy is enhanced in the case of Dox-loaded carriers on MG-63 (osteosarcoma) cell lines. The anticancer activity is tested in vivo on both male and female albino mice. Enhanced chemotherapeutic potential is observed for Dox-loaded Sr, Fe-HAp in a metastatic model of MG-63. The platinum derivative polymer possesses its own therapeutic effect and contributes to the general activity. The novel polymer-HAp nanohybrid represents an effective nanocarrier for the treatment of osteosarcoma.